THE EFFECT OF VARIED CONCENTRATION TAMARIND (Tamarindus indica L) EXTRACT AND THE SOAKING TIME ON THE REDUCTION LEVEL OF HEAVY METALS PLUMBUM (Pb) AND CADMIUM (Cd) IN THE CLAM (Anadara granosa) BLOOD - Lydia Mia Edina; Sumarto '; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aimed to determine the optimum concentration of tamarind extract and soaking time to reduce the heavy metals Pb and Cd in the blood of clam (Anadara granosa). The research was used the experimental method and designed as Factorial Completely Randomized Design. The clam was soaked into the solution of tamarind extract at 4 level concentrations, namely: without extract tamarind (K0), 10% tamarind (K10), 15% tamarind (K15), and 20% tamarind (K20), combined to 3 varied soaking time, namely: 60 minutes (W60), 90 minutes (W90), and 120 minutes (W120). All samples were assessed for their organoleptic characteristics and their metal Pb and Cd levels. The results showed that the treatment of soaking the clam into the 20% tamarind extract for 90 minutes was indicated the best treatment. It showed that the reduction of heavy metal up to the lowest level, those were Pb at 66,33% and Cd at 76,63%. Soaked clam blood soaked into the tamarind extract was affecting to their organoleptic characteristic, included to their consistence, taste and texture. The higher concentration of tamarind and the longer soaking time, the more little blackish brown and pale their consistance and the more acid tasted and quite clay of their texture.Keywords: Anadara granosa, concentration, heavy metals, soaking time Tamarindus indica L,